2011
DOI: 10.1007/s12640-011-9248-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Soman Exposure on GABAA Receptors in Rat Hippocampal Slices and Cultured Hippocampal Neurons

Abstract: Exposure of the central nervous system to organophosphorus (OP) nerve agents causes seizures and neuronal cell death. Benzodiazepines are commonly used to treat seizures induced by OPs. However, it is known that soman-induced seizures are particularly resistant to benzodiazepine treatment, as compared with other OPs. This study investigated the effect of soman on γ-aminobutyric acid (GABA) neurotransmission in acute rat hippocampal slices and the surface expression of GABA(A) receptors in cultured rat hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that soman administered directly to brain slices (Wang et al, 2011), or epileptiform activity and SE induced by other mechanisms (Goodkin et al, 2008; Goodkin et al, 2005; Naylor et al, 2005) lead to internalization of GABA A receptors in the hippocampus and reduced effectiveness of GABA agonists. However, recovery in the expression of GABA A receptors has also been observed to occur rapidly upon cessation of SE (Naylor, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that soman administered directly to brain slices (Wang et al, 2011), or epileptiform activity and SE induced by other mechanisms (Goodkin et al, 2008; Goodkin et al, 2005; Naylor et al, 2005) lead to internalization of GABA A receptors in the hippocampus and reduced effectiveness of GABA agonists. However, recovery in the expression of GABA A receptors has also been observed to occur rapidly upon cessation of SE (Naylor, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, benzodiazepines exhibit a time-dependency for efficacy to stop SE caused in part by the internalization of post-synaptic GABA A Rs (Naylor et al, 2005; McDonough et al, 2009, 2010). Soman exposure is reported to elicit reduced GABA A R function in rat brain (Lallement et al, 1993) and reduced surface expression of GABA A Rs specifically in the hippocampus (Wang et al, 2011). In vitro studies with soman in hippocampal slices suggest that a 30% reduction of surface expression of GABA A Rs renders hippocampal neurons unresponsive to diazepam (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Soman exposure is reported to elicit reduced GABA A R function in rat brain (Lallement et al, 1993) and reduced surface expression of GABA A Rs specifically in the hippocampus (Wang et al, 2011). In vitro studies with soman in hippocampal slices suggest that a 30% reduction of surface expression of GABA A Rs renders hippocampal neurons unresponsive to diazepam (Wang et al, 2011). These remaining GABA A Rs may be extrasynaptic receptors responsible for setting the background tone of global neuronal inhibition (Farrant and Nusser, 2005; Chuang and Reddy, 2018).…”
Section: Introductionmentioning
confidence: 99%